Supplemental levels of iron and calcium interfere with repletion of zinc status in zinc-deficient animals. Issue 5 (22nd April 2016) - Jayalakshmi, S.; Platel, Kalpana
Abstract : Negative interactions between minerals interfering with each other's absorption are of concern when iron and calcium supplements are given to pregnant women and children. Abstract : Negative interactions between minerals interfering with each other's absorption are of concern when iron and calcium supplements are given to pregnant women and children. We have previously reported that supplemental levels of iron and calcium inhibit the bioaccessibility of zinc, and compromise zinc status in rats fed diets with high levels of these two minerals. The present study examined the effect of supplemental levels of iron and calcium on the recovery of zinc status during a zinc repletion period in rats rendered zinc-deficient. Iron and calcium, both individually and in combination, significantly interfered with the recovery of zinc status in zinc deficient rats during repletion with normal levels of zinc in the diet. Rats maintained on diets containing supplemental levels of these two minerals had significantly lower body weight, and the concentration of zinc in serum and organs was significantly lower than in zinc-deficient rats not receiving the supplements. Iron and calcium supplementation also significantly inhibited the activity of zinc-containing enzymes in the serum as well as liver. Both iron and calcium independently exerted this negative effect on zinc status, while their combination seemed to have a more prominent effect, especially on the activities of zinc containing enzymes. This investigation is probably the first systematic study on the effect of these two minerals on the zinc status of zinc deficient animals and their recovery during repletion with normal amounts of zinc.